La exposición aguda a altitud previene el estrés oxidativo por una movilización del alpha-tocoferol plasmático - Casals, C.; Gomes, S. N.; López Contreras, G.; Rosillo, S.; Aragón Vela, J.; de Teresa, C.; Huertas, J. R. (Archivos de medicina del deporte, 2013)
Introduction: There is a controversy concerning to the modulation of hypoxia-induced oxidative stress; in addition, most studies covered mechanism of adaptation to altitude after an acclimation period, and they did not test the eff ects of acute exposures to hypoxia. Thus, the aim of the study was to establish oxidative status of trained swimmers analyzing the eff ects of exercise and acute exposure to moderate altitude. Materials and methods: Ten well-trained swimmers (5 females, 5 males) performed two similar mild-intensity training sessions of 90 minutes, one at an altitude of 630 m (normoxia) and the second of 2320 m (hypoxia). Training sessions were regulated to generate blood lactate values slightly higher than anaerobic threshold. 5 ml of blood samples were collected before and immediately after the exercise. Plasma were obtained by blood-centrifugation, samples were stored at -80ºC until analysis. Lipid peroxidation markers were hydroperoxides and thiobarbituric acid reactive substances (TBARS). Alpha-tocopherol was analyzed as non-enzymatic antioxidant mechanism. Comparisons between means were performed using one-way ANOVA. Results: Acute exposure to hypoxia produced a signifi cant decrease of TBARS (20.78±8.36 nmol/ml, p<0.03) and, after eff ort, of hydroperoxides (20.78±8.36 nmol/ml, p<0.03) in men. In swimmers of both sexes, plasmatic .-tocopherol significantly decreased by hypoxia (men: 23.06±4.26 nmol/ml, women: 19.51±4.26 nmol/ml, p<0.001). In normoxia condition, women presented lower concentrations of TBARS (20.54±8.36 nmol/ml, p<0.03) and hydroperoxides (2.16±0.87 nmol/ml, p<0.03) than men. Mild-intensity training session did not modify oxidative stress in well-trained swimmers. Conclusions: In previous studies we demonstrated a non-enzymatic antioxidant mobilization from plasma to muscular and hepatic tissues as a response to an oxidative stress situation. Therefore, we conclude that acute exposure to moderate altitude could prevent oxidative stress in swimmers by a fast mobilization of plasmatic alpha-tocopherol.